Challenges of deepening political commitment and long-term legitimacy in West African integration and the future of ECOWAS - Sampson Edodi; Frank Ahimbisibwe (Cogent Social Sciences, 2024)
Regional cooperation and integration are increasing globally with regional blocs working towards economic and political stability. In this paper, the nonsituational concept of political commitment and the pathway of normative legitimacy are employed to explore the model for deepening political integration in West Africa. The focus is on identifying key policy areas to enable consistent political commitment and long-term legitimacy in the West African integration. The article addresses this issue by employing a qualitative technique. Results show that ECOWAS policymakers must embrace the awareness that political integration is embedded in the 1993 Revised Treaty; voiding selective implementation of policies is critical for regional development; prioritize harmonization of preferences and compatibility of regional vs national interests; religious intolerance deepens the dilemma concerning religion and politics in West Africa; and an enabling environment for ECOWAS people is needed to make human rights respecting choices against the backdrop of freedom to choose terrorism or kidnapping for ransom as a means of livelihood. The paper shows that ECOWAS cannot be fighting politically and cooperates economically and should work to ensure a robust political union through a consistent political commitment and long-term legitimacy to achieve meaningful economic integration, peace and prosperity and the ECOWAS of peoples.